Perspectives for the analysis of arterial hypertension morbidity in Saratov region - Zhuzhlova N.Y.; Sazanova G.Y.; Dolgova E.M. (Саратовский научно-медицинский журнал, 2015)
Purpose: the study of trends in overall morbidity and primary hypertension in the Saratov region over the period from 2002 to 2013. Materials and methods. The official statistics Ministry of Health and the Federal State Statistics Service were used, which is processed using analytical and statistical methods. Results. The article has been providing the analysis of total and primary arterial hypertension morbidity of the population of the Saratov region, which is in accordance with the degree of the Government of the Russian Federation from December 1, 2004, N 715 to the group of socially significant diseases. During the period from 2002 to 2013 in the Saratov region, as well as in the Russian Federation in Volga Federal district, the tendency of growth of the overall incidence and the decrease in the primary incidence of arterial hypertension. Conclusion. The dynamics of incidence of hypertension suggests the need for careful analysis and optimization of medical care for patients with hypertension